Some Identities of the Frobenius-Euler Polynomials - Taekyun Kim; Byungje Lee (Abstract and Applied Analysis)
By using the ordinary fermionic p-adic invariant integral on ℤp, we derive some interesting identities related to the Frobenius-Euler polynomials.